Polyherbal Microemulgels as Potential Therapeutic Agents for Psoriasis: In Vivo and In Vitro Evaluation - Author- Ande S. N., Kshirsagar M. D. , Chandewar A. V., Kochar N. I. , Mohale D. S. (South Eastern European Journal of Public Health, 2025)
Objective This research aimed to investigate the therapeutic potential of two polyherbal microemulsion gel formulations, ABC (encompassing Azadirachta indica, Berberis aristata, and Coleus forskohlii) and BCG (comprising Boswellia serrata, Curcuma longa, and Glycyrrhiza glabra), in mitigating inflammation and restoring skin integrity in a psoriasis-like murine model triggered by UV-B irradiation and imiquimod (IMQ) application. Methods: Psoriasis-like inflammation was experimentally induced in Balb/c mice using a topical application of 5% imiquimod cream for seven consecutive days and in Wistar rats through UV-B irradiation for ten days. A control group, treatment groups that received 25 mg/kg of ABC or 50 mg/kg of BCG, and a conventional treatment group that received Clobetasol propionate were among the seven groups into which the animals were divided. Disease severity was evaluated using the Psoriasis Area Severity Index (PASI). Biochemical analyses measured pro-inflammatory cytokines such as TNF-α, IFN-γ, and VEGF, while histopathological studies examined epidermal structure and inflammatory cell infiltration, substantiating the anti-psoriatic efficacy of the formulations. Results: In vitro analyses demonstrated that both formulations exhibited stability and significant anti-inflammatory effects, with marked inhibition of pro-inflammatory cytokines (TNF-α, VEGF). In vivo, treatment with ABC and BCG substantially reduced PASI scores, with BCG at 50 mg/kg showing the most significant improvement, comparable to the positive control. Histological analysis confirmed reductions in epidermal thickening and inflammatory cell infiltration in treated groups. Conclusion: The polyherbal Microemulgel formulations ABC and BCG effectively reduced inflammation, cytokine levels, and epidermal thickening, demonstrating significant anti-psoriatic effects. These findings highlight the potential of these formulations as safe and effective alternatives for psoriasis treatment, warranting further investigation into their molecular mechanisms and clinical applications